2010
DOI: 10.1007/bf03208855
|View full text |Cite
|
Sign up to set email alerts
|

Sequence characteristics and divergent evolution of the chloroplastpsbA-trnH noncoding region in gymnosperms

Abstract: The psbA-trnH intergenic region is among the most variable regions in the gymnosperm chloroplast genome. It is proposed as suitable for DNA barcoding studies and is useful in phylogenetics at the species level. This region consists of two parts differing in their evolutionary characteristics: 1) the psbA 3’UTR (untranslated region) and 2) the psbA-trnH intergenic spacer. We compared the sequence and RNA secondary structure of the psbA 3’ UTR across gymnosperms and found consensus motifs correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…And, the psbA-trnH region has always been proposed as one of the popular DNA barcodes. 7,8,[10][11][12][13][14] However, DNA-based species identification using a large set of medicinal species of Fabaceae has not been carried out. Therefore, we examined the efficacy of using psbA-trnH in medicinal Fabaceae species determination across a wide taxon range.…”
mentioning
confidence: 99%
“…And, the psbA-trnH region has always been proposed as one of the popular DNA barcodes. 7,8,[10][11][12][13][14] However, DNA-based species identification using a large set of medicinal species of Fabaceae has not been carried out. Therefore, we examined the efficacy of using psbA-trnH in medicinal Fabaceae species determination across a wide taxon range.…”
mentioning
confidence: 99%
“…Some molecular techniques currently employed for the identification of medicinal plants are amplified fragment length polymorphism (Passinho-Soares et al, 2006), Restriction Fragment J. Plant Sci., 10 (4): 116-127, 2015 Length Polymorphism (RFLP) (Diao et al, 2009), random amplification of polymorphic DNA (Cao et al, 2010), Inter-simple sequence repeat (Tamhankar et al, 2009), Simple Sequence Repeat (SSR) (Sharma et al, 2008) and through microarray design (Carles et al, 2005;Jayasinghe et al, 2007;Zhu et al, 2008), which determine the variations of nucleotides in a DNA sequence belonging to the genome of plants, in particular of conserved sequences of genes present in the nucleus, mitochondria or chloroplast (Hao et al, 2008(Hao et al, , 2010a. These genomic fingerprints can differentiate between genera and species, demonstrating its usefulness for characterizing plants of medicinal interest and in consequence, the detection of possible adulterants.…”
Section: Conventional Methods For the Authentication Of Medicinal Plamentioning
confidence: 99%
“…This is the reason, why new techniques are required in order to identify possible contaminants or adulterants (plants contained in the product in addition to or as a substitute for the originally intended medicinal ones). Currently molecular tools are known that are used for the identification of polluting species of commercial products and can be proposed as an alternative for the quality control of plant preparations (Hao et al, 2010a;Chen et al, 2010).…”
mentioning
confidence: 99%
“…Contrast to this result, the nuclear ITS region to be very effective to identify the 8 Dalbergia species in the genus Dalbergia of Viet Nam [15]. However, the region trnH-psbA were proposed as DNA barcoding for species of Taxaceae [16,17], but previous research revealed that they were not suitable for a number of Dalbergia species in the family Fabaceae in Viet Nam [13]. The matK gene region is suggested as DNA barcoding in plants [18].…”
Section: Phylogeny Based On Gene Regionsmentioning
confidence: 99%
“…As announced by the group CBOL [19], the three gene regions of trnH-psbA, matK and trnL may be appropriate for the study of DNA barcoding in plants because they are exact clones of the target gene fragments by specific primers, and decoding their sequences may make it possible to distinguish plant taxa. Meanwhile, the trnH-psbA region [17,20] and the matK-barcode [21] have been proposed as DNA barcoding in plants. Our study reconfirmed the appropriate use of the three gene regions of matK, trnL and rpoC1 to discriminate the 15 coniferous species in Central Highland of Viet Nam ( Figure 3C, 3D and 3E).…”
Section: Phylogeny Based On Gene Regionsmentioning
confidence: 99%